Developmental and environmental effects on VTC2-dependent leaf ascorbate accumulation and functions - Kappel, Sandrine (Journal of experimental botany, 2025)
© The Author(s) 2025. Published by Oxford University Press on behalf of the Society for Experimental Biology.